2012
DOI: 10.1002/ange.201207554
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Overall Water Splitting Promoted by an α–β phase Junction on Ga2O3

Abstract: Gute Mischung: Ga2O3 mit einstellbaren α‐β‐Oberflächenphasengrenzen übertrifft einzelne α‐ oder β‐Ga2O3‐Oberflächenphasen bei der photokatalytischen Spaltung von Wasser in H2 und O2. Diese gesteigerte Leistung wird vor allem einer effizienten Ladungstrennung und einem effizienten Ladungstransfer über die α‐β‐Phasengrenze zugeschrieben.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 30 publications
3
93
1
1
Order By: Relevance
“…With the α–β phase junctions of Ga 2 O 3 , the figures of merit reached three‐ and sevenfold higher than that of the individual α‐Ga 2 O 3 and β‐Ga 2 O 3 phases. Moreover, the photocatalytic activity of the α–β phase junction samples was much greater than that of mechanically mixed α‐Ga 2 O 3 and β‐Ga 2 O 3 samples, the latter of which had an activity almost equal to the summed individual activities of the α‐Ga 2 O 3 and β‐Ga 2 O 3 phases . Considering the microscopic analysis, it was demonstrated that neither the particle size nor surface area was believed to be the reason for achieving high photocatalytic activity, but rather the presence of the α–β phase junction.…”
Section: Spe For Energy Conversion and Environmental Treatmentmentioning
confidence: 96%
See 3 more Smart Citations
“…With the α–β phase junctions of Ga 2 O 3 , the figures of merit reached three‐ and sevenfold higher than that of the individual α‐Ga 2 O 3 and β‐Ga 2 O 3 phases. Moreover, the photocatalytic activity of the α–β phase junction samples was much greater than that of mechanically mixed α‐Ga 2 O 3 and β‐Ga 2 O 3 samples, the latter of which had an activity almost equal to the summed individual activities of the α‐Ga 2 O 3 and β‐Ga 2 O 3 phases . Considering the microscopic analysis, it was demonstrated that neither the particle size nor surface area was believed to be the reason for achieving high photocatalytic activity, but rather the presence of the α–β phase junction.…”
Section: Spe For Energy Conversion and Environmental Treatmentmentioning
confidence: 96%
“…Upon calcination, one can convert all other phases into the β‐Ga 2 O 3 phase, which is the most thermodynamically stable phase . Literature survey indicates that the overall photocatalytic water splitting reaction has been scrutinized deliberately on the α‐Ga 2 O 3 and β‐Ga 2 O 3 phases and their mixtures . Jin and co‐workers have investigated mixed‐phase γ/β‐Ga 2 O 3 as a photocatalyst to understand the effect of the phase junction on the overall water‐splitting reaction.…”
Section: Spe For Energy Conversion and Environmental Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] Therefore, enhancing charge separation, accelerating the transportation of electrons and preventing their recombination before they move to the surface active sites of the photocatalysts, and improving the light utilization play key roles in determining the solar energy to H 2 conversion efficiency. One of the effective strategies for charge transportation and recombination is to load lower work function materials (metals or other compounds) on the surface of semiconductors as co-catalyst, so that junctions can be formed after loading.…”
Section: Introductionmentioning
confidence: 99%